PENGARUH PARIWISATA TERHADAP PENINGKATAN EKONOMI MASYARAKAT DAN KELESTARIAN LINGKUNGAN - Putri Aulia Noor; Rosalina Kumalati; Ellyn Normelani (Pelantar Press, 2024)
This study aims to analyze the impact of tourism on community economic growth and its implications for environmental sustainability by employing a qualitative literature study through the review of journals, research reports, and relevant official documents. The findings indicate that tourism makes a significant contribution to the local economy through job creation, increased household income, the strengthening of MSMEs, and its crucial role in enhancing Regional Original Revenue (PAD). However, the growth of tourism also poses negative risks, such as pollution, ecosystem degradation, and the decline of natural resources if not managed sustainably. Therefore, the implementation of sustainable tourism and community-based tourism concepts offers a viable solution to balance economic benefits with environmental preservation, allowing the tourism sector to develop as an instrument of sustainable development that improves community welfare while safeguarding nature and local culture.